Did you advance? Did you back down? Human rights and affirmative actions for Indigenous peoples in Latin America - Angnes, Juliane Sachser; Ichikawa, Elisa Yoshie; Klozovski, Marcel Luciano; Freitas, Maria de Fátima Quintal de (Education Policy Analysis Archives, 2020)
This theoretical essay proposes to understand how the contemporary conception of Human Rights is configured, and from that, to articulate the affirmative actions for Indigenous peoples inserted in this conception. In other words, it reflects on how this process took place in Latin America, that is, whether these actions proposed in Latin America for Indigenous peoples adopt a perspective constituted by the “subject of law” being seen in its particularity and peculiarity, and whether there have been advances or setbacks. The results showed that, specifically, from the conceptions presented at the International Labor Organization (OIT) there was a break in the integrationist paradigm, showing a real advance in the expressions of these conceptions and the ways in which indigenous societies are understood, at least in the applied legislation in Latin America. However, there is still much to reflect on and fight for.